Clinical and biomarker trajectories in sporadic Alzheimer's disease: A longitudinal study. Issue 1 (12th August 2020) - Wang, Hui‐Fu; Shen, Xue‐Ning; Li, Jie‐Qiong; Suckling, John; Tan, Chen‐Chen; Wang, Yan‐Jiang; Feng, Lei; Zhang, Can; Tan, Lan; Dong, Qiang; Touchon, Jacques; Gauthier, Serge; et al.
Abstract: Introduction: Amyloid beta (Aβ) deposition was identified to precede tau pathology and neurodegeneration in familial Alzheimer's disease (AD). But the divergence between sporadic and familial AD limits the extension of these findings to sporadic AD. Methods: Longitudinal changes of biomarkers among different stages were assessed using linear mixed‐effects models. The slopes of the models were used to estimate rates of change to calculate the biomarker trajectories in sporadic AD. Results: Cerebrospinal fluid (CSF) Aβ was estimated to decline 45.2 years (abnormal: 27.8 years) before dementia, and Aβ deposition seemed to increase 31.7 years (abnormal: 26.7 years) before dementia. It was estimated to take 29.0 years (CSF t‐tau), 12.2 years (memory), 11.6 years (hippocampus), 9.3 years (hypometabolism), and 6.1 years (cognition) to move from normal to dementia. Discussion: The trajectory in sporadic AD is led by Aβ accumulation, followed by CSF t‐tau increase, memory deficits, brain atrophy, hypometabolism, and cognitive decline.